Fiction refracts science : modernist writers from Proust to Borges - Thiher, Allen, 1941- (University of Missouri Press, 2005)
"Examines the relationship between science and the fiction developed by modernists, including Musil, Proust, Kafka, and Joyce. Looks at Pascalian and Newtonian cosmology, Darwinism, epistemology, relativity theory, quantum mechanics, the development of modernist and postmodern fiction, positivism, and finally works by Woolf, Faulkner, and Borges"--Provided by publisher